Academic Resilience Skills: A Systematic Literature Review - Nuha, Moch. Syihabudin; Muslihati, Muslihati; Zamroni, Zamroni (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2024)
Academic resilience is defined as the ability of an individual to maintain his or her academic ability successfully and through various activities, difficulties, challenges, or obstacles in an academic context. Research on resilience has been widely found in other fields, so it has become commonplace, but in academic contexts, especially in Indonesia, it has become a hot topic related to academic success and student well-being. In the context of academic resilience, students must have some abilities that make them individually resilient. This is secondary research using a method of systematic literature review that goes through five main steps, ranging from literature search, research questions, data processing, filtering or selection of data, and conclusion of selected articles. The results show that students need to be trained in improving their resilience through both curative and preventive strategies, including peer-counseloring programs, group guidance and counseling, mindfulness approaches, and cognitive restructuring. The results of the research can be used as a source of reading for further research to investigate the extent to which the negative impact of this reduction of ability, any factors, and appropriate interventions can create a guide for class teachers as a strategy for improving student academic resilience. Because this ability also affects his academic achievement and success.